Genome Instability-Associated Long Non-Coding RNAs Reveal Biomarkers for Glioma Immunotherapy and Prognosis - Wang, Xinzhuang; Zhang, Hong; Ye, Junyi; Gao, Ming; Jiang, Qiuyi; Zhao, Tingting; Wang, Shengtao; Mao, Wenbin; Wang, Kaili; Wang, Qi; Chen, Xin; Hou, Xu; et al. (Frontiers in Genetics, 2022)
Genome instability is a hallmark of tumors and is involved in tumor proliferation, invasion, migration, and treatment resistance of many tumors. Moreover, long non-coding RNAs (lncRNAs) play an important role in this process. However, the relationship of genome instability with gliomas remains unclear. Therefore, we constructed a genome stability and gene instability framework based on somatic mutation data and found twenty-three lncRNAs related to genome instability in glioma. We then identified seven genome instability-derived lncRNA-based gene signatures (GILncSig). Multiple platforms were used to verify the GILncSig were closely related to patient prognosis and clinical characteristics. In addition, the GILncSig better predicted outcomes than that of single-gene mutations (IDH1, TP53, CIC, ARTX) or wild-type status. Finally, we found that GILncSig, the glioma microenvironment, and glioma cell DNA methylation-based stemness index (mDNAsi) interacted with each other to form a complex regulatory network. In summary, this study confirmed GILncSig was an independent prognostic indicator for patients, distinguished high-risk and low-risk groups, and affected immune-cell infiltration and tumor-cell stemness indicators (mDNAsi) in the tumor microenvironment, resulting in tumor heterogeneity and immunotherapy resistance. Basic experiments also revealed that GILncSig is related to the prognosis and clinical characteristics of patients with glioma. The TICA and pRRophetic databases also show that compared with patients in the low-risk group, patients in the high-risk group are relatively insensitive to immunotherapy, but are relatively sensitive to cisplatin and rapamycin. GILncSig are expected to provide new molecular targets for the clinical treatment of gliomas.